Evaluation of drinking water chlorination by-products and their relationship to induce mutagenesis (cell mutations) - Montero-Campos, Virginia (2014)
In the chlorination process produces a series of chemical reactions between the chlorine used in the disinfection and the organic matter present in the water to be treated. The nature and concentration of the compounds formed, are dependent physicochemical variables of soil organic matter, which react with chlorine added products originating from different compounds, are toxic, mutagenic and carcinogenic including, all together are known as chlorination byproducts (acronym SPD), which include compounds called trihalomethanes (THM’s). It was investigated the presence of these types of products in costa rican waters by the technique of solid phase microextraction (HEADSPACE / SPME Solid Phase Microextraction / GS-MS), using a Varian 450 Gas Chromatograph Mass Spectrometer coupled. It was analyzed 39 samples of water from local groundwater sources and surface water sources (full treatment plants) in users homes dispensed by treatment systems / Central Canton of Cartago and Costa Rican Water and Sewer Institute Plants of Moravia, Guadalupe and Pavas, with a total of 156 products identified and quantified corresponding these to: chloroform, bromodichloromethane, and tribromochloromethane dibromochloromethane. In water samples complete treatment systems found that 80 products was analyzed, 12 of these exceeded the maximum allowed according to National Regulations for Water Quality human consumption, while the aqueducts supplied by groundwater administered by the Municipality of Cartago, 76 products was analyzed, only one of them exceeded the maximum allowed.